Photocatalytic Degradation of Diazinon in Aqueous Solutions Using ZnO Under Visible Light Irradiation: An Advanced Oxidation Process Approach - Umam, Hilman Imadul; Pambudi, Teguh; Widianto, Eri; Yuliasari, Fitri; Putri, Fajar Amelia Rachmawati; Nandira, Rantika Sekar; Utami, Marsah Rahmawati (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Diazinon is a commonly used organophosphate insecticide in agriculture, but its persistence in water and soil presents significant health and environmental concerns. This study investigates the photocatalytic removal of diazinon from aqueous solutions using zinc oxide (ZnO) nanoparticles activated by visible light irradiation. ZnO was chosen due to its excellent photocatalytic properties, including a direct band gap ( 3.1 eV), strong oxidative capability, chemical stability, and non-toxic nature, making it a superior candidate for visible-light-driven environmental remediation. Photocatalytic degradation under sunlight was also assessed for comparison. Key operational parameters, such as photocatalyst dosage, solution pH, initial diazinon concentration, and irradiation time, were systematically optimized. The highest degradation efficiency degradation was achieved with 20 mg of ZnO, neutral pH, 30 mg/L an initial concentration, and 60 minutes of irradiation. Kinetic analysis revealed that the process followed zero-order reaction kinetics (k = 1.118; R2 = 0.9962). Notably, visible light irradiation was more effective than sunlight in degrading diazinon. These findings provide important details about the potential of ZnO nanoparticles as an efficient, low-cost, and environmentally friendly photocatalyst for remediating pesticide-contaminated water under sustainable energy conditions.